4D scale-dependent Schwarzschild-AdS/dS black holes: study of shadow and weak deflection angle and greybody bounding - Övgün, Ali; Pantig, Reggie C.; Rincon, Angel (Springer Heidelberg, 2023)
We investigate the shadow, deflection angle, and the greybody bounding of a Schwarzschild-AdS/dS black hole in scale dependent gravity. We used the EHT data to constrain the parameter epsilon. We have found that within the 1 sigma level of uncertainty, epsilon M-0 ranges at 10(-11) - 10(-16) orders of magnitude for Sgr. A*, and 10(-11) - 10(-17) for M87*. Using these parameters, we explored how the shadow radius behaves as perceived by a static observer. Using the known parameters for Sgr. A* and M87*, we found different shadow cast behavior near the cosmological horizon even if the same scaling parameters were used. We explored the deflection angle alpha circumflex expressionccent in the weak field limit for both massive and null particles, in addition to the effect of finite distances using the non-asymptotically flat version of the Gauss-Bonnet theorem. We have found that the alpha circumflex expressionccent strongly depends on massive particles. Tests on epsilon's effect using Sgr. A* is only along points of low impact parameters. For M87*, only the scaled BH in AdS type can be tested at high impact parameters at the expense of very low value for alpha( circumflex expressionccent ). We study the rigorous bound on the greybody factor for scalar field emitted from black holes in the theory and show the bound on the transmission probability. The effects of the scale-dependent gravity on the greybody factors are investigated, and the results indicate that the bound on the greybody factor in this case is less than the bound for the Schwarzschild black hole.
Keywords: Extreme Gravity Tests; Telescope Results. I.; Quasi-Normal Modes; Hawking Radiation; Dark-Matter; Parameter-Estimation; Gravitational-Waves; Relativistic Theory; Interior Solutions; Machs Principle